Relationship Between Export and Economic Growth: Evidence from West African Countries - Kulu, Evans (The Indian Economic Journal, 2024)
The export-led growth hypothesis (ELGH) postulates that export is a major driver of economic growth. This study tests this hypothesis and further analyses the determinants of exports in the case of West African countries. An annual panel data spanning from 2008 to 2018 was used. Findings from the system GMM and OLS estimations validate the ELGH in West Africa. The results also reveal that foreign direct investment, employment, remittances, land area and infrastructure are significant boosters of export while population, real effective exchange rate and taxes on international trade are detrimental to export performance in the region. The study recommends the relaxation of taxes especially on international trade to encourage businesses that produce to feed the export sectors, provide an enabling environment for businesses and also attract foreign investors.JEL Codes: F14, F21, O55
Keywords: Exchange Rate and Taxes; Foreign Direct Investment; International Trade; Economic Growth